HUBUNGAN EFIKASI DIRI DENGAN KESULITAN BELAJAR PADA PESERTA DIDIK KELAS XI DI MAN 2 SEMARANG - Anggraeni, Nuris (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2023)
The purpose of this study was to determine the relationship between self-efficacy and learning difficulties of class XI students at MAN 2 Semarang. This research is a quantitative research with correlational quantitative research methods. The study population was 140 students in class XI MIPA 1, XI MIPA 2, XI IPS 1 and XIIPS 2. The samples used were students of class XI MIPA2, XI IPS1 and XI IPS 2 with a total of 105 students. The class used for the tryout was class XI MIPA 1 with a total of 35 students. The technique used is a saturated sampling technique. The tools used in data collection are in the form of a self-efficacy scale and a learning difficulty scale. The results of the correlation analysis between self-efficacy and the difficulty of learning to obtain the value of the product moment correlation coefficient obtained r calculate < r table 0.535 < 0.192 significance value 0.000 < 0.05 which means that the two variables are correlated. Then the value of the result correlation coefficient (r)-0.535 with a negative level, it can be concluded that there is a significant perfect negative relationship between self-efficacy and class XI learning difficulties in MAN 2 Semarang at the level of 5% (0.05). Keywords: Self-Efficacy, Learning Difficulties